2023
DOI: 10.1007/s11207-023-02142-5
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Elemental Abundances During A-Class Solar Flares Observed by Chandrayaan-2 XSM

Abstract: The abundances of low First Ionisation Potential (FIP) elements are three to four times higher (FIP bias) in the closed loop active corona than in the photosphere, known as the FIP effect. Observations suggest that the abundances vary in different coronal structures. Here, we use the soft X-ray spectroscopic measurements from the Solar X-ray Monitor (XSM) on board the Chandrayaan-2 orbiter to study the FIP effect in multiple A-class flares observed during the minimum of solar cycle 24. Using time-integrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…XSM provides full-disk spectral data, but the XRT capabilities have allowed us to probe the AR and small flare of interest. We found evidence of elemental abundances decreasing toward photospheric values around the flare peak time while remaining at coronal values before and after the peak time, consistent with results previously studied and reported from XSM (Mondal et al 2021;Mithun et al 2022;Nama et al 2023) and MinXSS (Woods et al 2017).…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…XSM provides full-disk spectral data, but the XRT capabilities have allowed us to probe the AR and small flare of interest. We found evidence of elemental abundances decreasing toward photospheric values around the flare peak time while remaining at coronal values before and after the peak time, consistent with results previously studied and reported from XSM (Mondal et al 2021;Mithun et al 2022;Nama et al 2023) and MinXSS (Woods et al 2017).…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…XSM also observed multiple flaring in ARs and these data have been used to study the time evolution of the plasma parameters during A-class, B-class, and C-class flares (Mondal et al 2021;Mithun et al 2022;Nama et al 2023). These studies show that during the impulsive phase, the temperature of the flaring plasma reaches a few MK, whereas elemental abundances show a sharp transition from coronal to close to photospheric values.…”
Section: Introductionmentioning
confidence: 95%
“…These ARs produced many small B/A-class flares, seen as multiple spikes in the XSM light curves. Detailed studies of these small flares were reported by Mondal et al (2021) and Nama et al (2023).…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…When ARs were present on-disk, XSM recorded hundreds of small flares of different classes. Elemental abundance variations during these small flares were found, for the first time, to initially drop toward photospheric values, then rapidly return to coronal values, as described by Mondal et al (2021), Mithun et al (2022), andNama et al (2023). In this paper, we analyze the temporal evolution of ARs outside of flaring activity, and for this, we have chosen to study three isolated ARs: AR 12749, AR 12758, and AR 12759.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…We assume solar photospheric abundances (Asplund et al 2009) in both the radiative losses and forward model, which is consistent with observations of large solar flares (Warren 2014). Recent observations have additionally found that abundances of some elements (with low first ionization potential) vary with time during a flare, from coronal abundances toward photospheric in the impulsive phase, and then back toward coronal during the gradual phase (Mondal et al 2021;Nama et al 2023;Sylwester et al 2023). Additionally, abundances can vary spatially (Doschek & Warren 2016) and from flare to flare (Sylwester et al 1998).…”
Section: Modelmentioning
confidence: 99%